Taxonomic revision of the genus Ononis (Trifolieae, Fabaceae) in Egypt, with the first record of Ononis viscosa subsp. breviflora - Fayed, Abdel Aziz A.; El-Hadidy, Azza H.; Faried, Ahmed M.; Olwey, Asmaa O. (Phytotaxa, 2019)
The genus Ononis comprises 86 species worldwide distributed in temperate regions. It is represented in Egypt by ten species. During recent excursions to the mountains of southern Sinai Peninsula, a newly recorded species, namely O. viscosa subsp. breviflora, was collected. This new record was previously confused with O. sicula. These two species can be differentiated by corolla length and shape. This study provides a full taxonomic revision of the genus for the flora of Egypt, updated nomenclature for all taxa, amended descriptions, detailed hand drawings, and a diagnostic key to the species. The most valuable diagnositic characters in the taxonomy of the genus in Egypt are discussed. After critical examination and literature study, we found that two names (O. serrata and O. vaginalis) needed to be lectotypified.